POLITIK HUKUM PERLINDUNGAN LAHAN PERTANIAN DAN HAK ASASI PETANI SEBAGAI INSTRUMEN MEWUJUDKAN KETAHANAN PANGAN BERKELANJUTAN DI INDONESIA - Sirajuddin, Afwit Freastoni dan (Jurnal Konstitusi, 2010)
The legal politic of protecting Sustainable Food Agricultural Land as an effort to prevent the conversion of wet land and to protect the farmers’ rights is difficult to do. However, the real effort is to establish a set of firm regulations. In some contexts, there are still some weaknesses in the policies made by the government in maintaining the land. Moreover, in its implementation, potential conflicts of interests between local governments that base their reasons on local autonomy and the central government that intends to protect food agricultural lands may happen. The legal politic of protecting Sustainable Food Agricultural Land as an effort to prevent the conversion of wet land and to protect the farmers’ rights is difficult to do. However, the real effort is to establish a set of firm regulations. In some contexts, there are still some weaknesses in the policies made by the government in maintaining the land. Moreover, in its implementation, potential conflicts of interests between local governments that base their reasons on local autonomy and the central government that intends to protect food agricultural lands may happen.